68.0k views
0 votes
Helppp! Solve for x!​

Helppp! Solve for x!​-example-1
User ACC
by
6.1k points

2 Answers

8 votes


\qquad \qquad\huge \underline{\boxed{\sf Answer}}

Here we go ~


\qquad \sf  \dashrightarrow \: 6 {}^( - 2x + 1) = 36


\qquad \sf  \dashrightarrow \: {6}^( - 2x + 1) = {6}^(2)

now, let's apply logarithm on both sides with base (6)


\qquad \sf  \dashrightarrow \: log_(6)( 6 {}^( - 2x + 1) ) = log_(6)( {6}^(2) )

According to properties of logarithm, the exponent on the number come out and it's written as a product of exponent times the logarithm.

that is :


\sf [ log_(a)(b {}^(n) ) = n * log_( a )(b) ]


\qquad \sf  \dashrightarrow \: ( - 2x + 1) * log_(6)(6) = 2 * log_(6)(6)

now, as we know : when the base and argument of log are same, then value of log is 1


\qquad \sf  \dashrightarrow \: - 2x + 1 = 2


\qquad \sf  \dashrightarrow \: - 2x = 2 - 1


\qquad \sf  \dashrightarrow \: - 2x = 1


\qquad \sf  \dashrightarrow \: x = - (1)/(2)

User Sagnik
by
7.0k points
6 votes

Solution:


  • 6^(-2x + 1) = 36
  • =>
    (6)6^(-2x) = 36
  • =>
    6^(-2x) = 6
  • =>
    -2x = 1
  • =>
    x = (-1)/(2)

The solution for this equation is -1/2.

User Zafer
by
7.9k points